2018
DOI: 10.1080/21645515.2018.1520581
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant TSA-1 and evaluation of its potential for the immuno-therapeutic control ofTrypanosoma cruziinfection in mice

Abstract: A therapeutic vaccine for human Chagas disease (American trypanosomiasis caused by Trypanosoma cruzi) is under development based on the success of vaccinating mice with DNA constructs expressing the antigens Tc24 and Tc-TSA-1. However, because DNA and nucleic acid vaccines produce less than optimal responses in humans, our strategy relies on administering a recombinant protein-based vaccine, together with adjuvants that promote Th1-type immunity. Here we describe a process for the purification and refolding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Thus, the effectiveness of a Chagas disease vaccine could depend on the efficiency with which the primed immune system prevents T. cruzi from reaching the relative safety of these sites of persistence, and its ability to maintain this response over time against a wide range of strains. The results presented here, and elsewhere [31-34, 45, 46, 53-58], highlight the possibility that current subunit/DNA vaccines may be unable to fulfil these requirements under the schedules used for administration, although their ability to prevent lethal outcomes [31-34, 45, 46, 54, 57] and provide therapeutic benefits [33,[53][54][55][56]58] merits further research. In addition, the long-term protection conferred by a drug-cured live infection suggests that the use of parasites, suitably attenuated by genetic modification, may be an approach worth exploring to identify an effective vaccine.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 67%
“…Thus, the effectiveness of a Chagas disease vaccine could depend on the efficiency with which the primed immune system prevents T. cruzi from reaching the relative safety of these sites of persistence, and its ability to maintain this response over time against a wide range of strains. The results presented here, and elsewhere [31-34, 45, 46, 53-58], highlight the possibility that current subunit/DNA vaccines may be unable to fulfil these requirements under the schedules used for administration, although their ability to prevent lethal outcomes [31-34, 45, 46, 54, 57] and provide therapeutic benefits [33,[53][54][55][56]58] merits further research. In addition, the long-term protection conferred by a drug-cured live infection suggests that the use of parasites, suitably attenuated by genetic modification, may be an approach worth exploring to identify an effective vaccine.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 67%
“…27 Previous studies have demonstrated the ability of E6020 alone or formulated together with T cruzi recombinant antigens, including Tc24-C4 and TSA-1, in a squalene emulsion to decrease cardiac parasite burdens and increase survival of BALB/c mice with acute T cruzi infection. 24,31,32 Additional studies have confirmed the immunogenicity of T cruzi vaccines formulated with E6020 in Rhesus macaques. 41 However, little is known about the dose-ranging effect of this TLR-4 agonist and its ability to confer protection against cardiac damage.…”
mentioning
confidence: 87%
“…Preclinical studies assessing different doses, formulations and adjuvants for a vaccine against CD have been conducted showing promising results in their ability to induce a strong cellular immunity and confer protection against acute and chronic infection in murine models. 19,[24][25][26][27][28][29][30] To date, our lead vaccine candidate consists of a genetically modified parasite-derived recombinant protein Tc24-C4, a version of the T cruzi-derived flagellar calcium-binding protein. Four cysteines were mutated to improve stability, and combined with a TLR4 agonist adjuvant, this antigen is delivered in a stable emulsion.…”
mentioning
confidence: 99%
“…So far, production processes for recombinant Tc24 and TSA-1 antigens are the only ones to undergo extensive process development and quality control. Specific mutations of cysteine residues were engineered in both antigens, to increase protein stability and yield, without compromising antigenicity, and scalable fermentation and purification steps have also been optimized and may be transferred for GMP production [ 45 , 46 , 94 , 95 ].…”
Section: Challenges and The Way Forwardmentioning
confidence: 99%